Tinjauan Yuridis Penanggulangan Tindak Pidana Kecelakaan Lalu Lintas Oleh Anak Yang Mengakibatkan Matinya Korban - Rudi Anto Sinaga (Albayan Journal of Islam and Muslim Societies, 2024)
This study aims to determine the discretion in traffic crimes that result in the loss of life of others by children, the implementation of police discretion, as well as obstacles and efforts in its application. The research method uses a normative and empirical legal approach. The normative study examined Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA) and Law No. 2 of 2002 concerning the Indonesian National Police. The empirical study was conducted by examining the practice of police discretion, particularly at the Indrapura Police Station. The results of the study show that the legal basis for police discretion is found in Article 18 paragraph (1) of the Police Law, which gives the authority to act according to one's own judgment in the public interest. In practice, the police apply a restorative justice model through Alternative Dispute Resolution (ADR) in the form of mediation between the child offender and the victim's family. This mechanism aims to protect the best interests of the child while restoring social relations. The obstacles that arise are the choice of imprisonment or fines as sanctions, where the community prefers fines so as not to cause a deterrent effect, as well as the negative perception of children towards the police due to a lack of legal understanding. In conclusion, police discretion in juvenile traffic cases prioritizes restorative justice, but its effectiveness is limited due to obstacles in legal awareness and the weakness of the applicable sanctions.